2021
DOI: 10.1002/adsc.202100491
|View full text |Cite
|
Sign up to set email alerts
|

C1‐Symmetric Atropisomeric NHC Palladium(II) Complexes: Synthesis, Resolution and Characterization

Abstract: Series of chiral palladium(II) allyl and cinnamyl complexes bearing a C 1 -symmetric N-heterocyclic carbenes were synthesized from achiral precursors. The chirality of theses complexes results from the formation of the carbene-palladium bond which restricts the rotation of dissymmetric N-aryl substituents of the NHC and thus creates an axis of chirality. Chiral HPLC at preparative scale enabled the resolution of racemic complexes and provided a straightforward access to complexes with excellent enantiopurities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…With copper(I) and silver(I), complexes 5a and 6a , configuration stabilities should be significantly reduced and even if the observation of enantiomers by chiral HPLC analysis was expected, the isolation of enantiopure complexes by cHPLC in a preparative scale might be troublesome. Theoretical calculations suggested that the more favorable rotation would take place on the metal side as it was concluded from our previous studies 22,23 …”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…With copper(I) and silver(I), complexes 5a and 6a , configuration stabilities should be significantly reduced and even if the observation of enantiomers by chiral HPLC analysis was expected, the isolation of enantiopure complexes by cHPLC in a preparative scale might be troublesome. Theoretical calculations suggested that the more favorable rotation would take place on the metal side as it was concluded from our previous studies 22,23 …”
Section: Resultsmentioning
confidence: 69%
“…With an unsubstituted backbone, unsaturated (complexes 1) or saturated (complexes 2), enantiomers could not be observed by cHPLC analyses suggesting low rotational barriers values. 23 This statement was confirmed by theoretical calculations, which allowed to quantify enantiomerization barriers with a reasonable level of confidence in addition to predict on which side the most favorable rotation will take place.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations